Numerical Investigation of Square Footing Positioned on Geocell Reinforced Sand by using ABAQUS Software - Juneja, Gaurav; Sharma, Ravi Kumar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The usage of geocell reinforcement for foundations supported on weak soil has been increased these days. The purposed study uses FEM-based ABAQUS software to analyse the behaviour of square footing supported on geocell reinforced sands subjected to static vertical loading. Numerical analysis was performed to find the optimum combination of the different geometric parameters of the geocell reinforcement.
Keywords: square footing; geocell reinforcement; weak soil; numerical investigation; MES; ABAQUS; software; ława fundamentowa; zbrojenie; słabe grunty; badania numeryczne